Genetic variability of human papillomavirus type 39 based on E6, E7 and L1 genes in Southwest China - He, Jiaoyu; Li, Tianjun; Wang, Youliang; Song, Zhilin; Li, Qiufu; Liu, Yiran; Cui, Yanru; Ma, Siyu; Deng, Junhang; Wei, Xia; Ding, Xianping (Virology journal, 2021)
Human papillomavirus type 39 associated with genital intraepithelial neoplasia and invasive cancers, has a high prevalence in Southwest China. HPV E6, E7 are two main papillomavirus oncoproteins, closely relate to the function of HPV immortalization, cell transformation, and carcinogenesis. L1 is the major capsid protein, can reflect the replication status of the virus in cells and the progression of cervical lesions. The purpose of this study is to reveal the prevalence of HPV 39 and the genetic polymorphisms of HPV39 based on E6, E7 and L1 gene in southwest China. Cell samples were collected by cervical scraped for HPV detecting and typing, and HPV39 positive samples were selected out. Important E6, E7 and L1 genes of HPV39 were sequenced and analyzed for the study of HPV39 genetic polymorphisms. Phylogenetic trees were constructed by Maximum-likelihood and Kimura 2-parameters methods in Molecular Evolutionary Genetics Analysis version 6.0. The selection pressures of E6, E7 and L1 genes were estimated by Datamonkey web server. The secondary and three-dimensional structure of HPV39 E6, E7 proteins were created by sopma server and SWISS-MODEL software. 344 HPV39 positive samples were selected from 5718 HPV positive cell samples. Among HPV39 E6-E7 sequences, 20 single nucleotide mutations were detected, including 10 non-synonymous and 10 synonymous mutations; 26 single nucleotide mutations were detected in HPV39 L1 sequences, including 7 non-synonymous and 19 synonymous mutations respectively. 11 novel variants of HPV39 E6-E7 (5 in E6 and 6 in E7) and 14 novel variants of HPV39 L1 were identified in this study. A-branch was the most frequent HPV39 lineage in southwest China during our investigation. Selective pressure analysis showed that codon sites 26, 87, 151 in E6 and 75, 180, 222, 272, 284, 346, 356 in L1 were positively selected sites, as well as codon sites 45, 138, 309, 381 were negative selection sites in L1 gene, E7 has neither positive selection sites nor negative selection sites. A certain degree of secondary and three-dimensional structure dislocation was existed due to the non-synonymous mutations. Amino acid substitution affected the secondary and three-dimensional structure of HPV39, and resulting in the differences of carcinogenic potential and biological functions as well as the immune response due to the antigen epitopes difference, the antigen epitopes with stronger adaptability in Southwest will be screened out based on the above research results for the later vaccine development. And gene polymorphism of HPV39 in Southwest China may improve the effectiveness of clinical test and vaccine design, specifically for women in Southwest China.